PENERAPAN MODEL PROBLEM BASED LEARNING BERBANTUAN MEDIA ZIG-ZAG DALAM PEMBELAJARAN PENDIDIKAN PANCASILA DI SD PANCASILA - Dyah Pramesti Mustikasari; Radita Hasanah; Susilo Tri Widodo; Fauzia Ulfa (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This research aims to determine the effectiveness of the Problem Based Learning model using zig-zag media on Pancasila Education Learning Class IV at Pancasila Elementary School, Semarang City. This research uses the Classroom Action Research (PTK) method with a qualitative and quantitative approach. This research consists of two cycles, each cycle consisting of planning, implementation, observation and reflection activities. The subjects of this research were fourth grade students at SD Pancasila, Semarang City. The sampling technique used total sampling. Quantitative data from the research results were analyzed in a descriptive manner, namely calculating the number, calculating the average, calculating the percentage value, calculating the smallest value and making a graph. From the results of the analysis it can be concluded that the Problem Based Learning learning model with media zig-zag is effective in learning Pancasila and Citizenship Education (PKn) Class IV Pancasila Elementary School, Semarang City.